Desain Kebijakan City Branding Daerah : (Studi di Kabupaten Blitar, Provinsi Jawa Timur, Indonesia) - Muhammad Lukman Hakim (Sawala : Jurnal Administrasi Negara, 2024)
This research focuses on the design of city branding policies in Blitar Regency, East Java Province, Indonesia. Each region is responsible for enhancing its image through promotion and branding as a strategy to attract public and tourist attention. Blitar Regency proves that city branding can have a positive impact on the tourism sector, regional sustainability, and the welfare of its residents. The rebranding effort of tourism with the tagline "Blitar Land of Kings" has yielded positive results by facilitating recognition and increasing the attractiveness of Blitar Regency. The concept of holistic and integrated city branding becomes an important focus, referring to the City Brand Hexagon theory proposed by Simon Anholt. This research uses a literature study method to explore the elements of measuring the effectiveness of city branding in Blitar Regency. By using secondary data sources in the form of official government documents and scientific literature, this research is expected to provide a deep understanding of the impact and effectiveness of the branding strategy applied by Blitar Regency in attracting attention and increasing tourist visits.